Violence against Women Living with HIV: A Cross Sectional Study in Nepal - Aryal, Nirmal (Glob J Health Sci, 2012)
BACKGROUND: Violence against Women (VAW) and Human Immunodeficiency Virus (HIV) both constitute major public health issues and there is an increasing evidence of their intersection. Data are sparse on the intersection of VAW and HIV in South Asia region. We aimed to identify different forms and magnitude of violence incurred by women living with HIV, and analyse causes and consequences. METHODS: A cross-sectional study was conducted among 43 HIV positive women in three districts of Nepal, in the period of March-May 2008. Data was collected through semi-structured interview questionnaire. RESULTS: The vast majority of the participants (93.02%) had suffered from at least one form of the violence. The prevalence of violence rose up sharply after being diagnosed with HIV positive than before (93.02% vs.53.5%). Forty-five percent of the participants reported their husbands being main perpetrator of violence. Self-humiliation and health and treatment problem were the major consequences of violence as reported by 90% and 77.5% of the participants respectively. CONCLUSION: Violence was observed to be highly prevalent among women living with HIV in Nepal. Further larger and nationally representative researches are imperative to better understand the cross-section between VAW and HIV. Our finding recommends to prioritizing programs on social aspects of HIV such as violence.